Evaluating Interventions that Improve Participation in Chores in Children and Youth with Disabilities: A Systematic Review. Issue 3 (3rd July 2021) - Laverdure, Patricia; Nemec, Emily; Johnson, Connie; Blake, Tammy
ABSTRACT: The purpose of this systematic review is to describe current evidence regarding interventions that improve the participation and performance of chores in children and youth with disabilities from the ages of 3 to 21. A systematic review of articles published between 2000 and 2019 was conducted using the PRISMA-P systematic review methodology. An a priori PICO framework was used to search databases, article reference lists, and selected journals. Chosen articles were annotated, evaluated for risk of bias, and synthesized to develop recommendations for school and early intervention practitioners. Titles and abstracts of 632 articles were reviewed and 7 articles that evaluated interventions that improve performance of chores in children and youth met inclusion criteria. There is evidence to support the use of occupation-based intervention, care-giver coaching, cognitive-behavioral strategies, and technology supports in occupational interventions to improve performance of chores in children and youth with disabilities and improve their long-term outcomes.